METHODOLOGY FOR DEVELOPING STUDENTS’ DIALOGIC SPEECH COMPETENCE - Komilova Mukhtasar Abdunabi qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The development of dialogic speech competence in students is a critical component of modern education, as it fosters effective communication, critical thinking, and social interaction skills. This methodology focuses on creating an interactive learning environment where students actively engage in dialogue, express their ideas, and respond to others in meaningful ways. By emphasizing collaborative learning and practical communication scenarios, this approach allows students to enhance their ability to participate in conversations, negotiate meaning, and build mutual understanding.